Empowering Financial Well-Being through Financial Literacy: A Comparative Analysis of Welfare Recipients and Non-Recipients in Gaya District, Bihar - Raj Aman; Nayak Santosh Kumar; Kumbhar Rathi Kanta (Studia Ekonomiczne i Regionalne)
This study seeks to enhance financial well-being by offering valuable insights into the financial literacy of both welfare recipients and non-recipients in Gaya, Bihar.